Squat lobsters (Crustacea: Decapoda: Anomura: Galatheoidea) from off the northwestern coast of the Baja California Peninusla, Mexico - Hendrickx, Michel E. (Zootaxa, 2021)
Four species of squat lobsters were collected off the northwestern coast of the Baja California Peninsula, Mexico, during an exploratory survey of fishing resources. Janethogalathea californiensis, described from California was previously known from off the west coast of the Baja California Peninsula (two localities) and from the Gulf of California (three localities). Of the three species of Munida collected during the survey, M. tenella is recorded off the west coast of the Baja California Peninsula for the first time. These are the fourth record of M. hispida and the second record of M. quadrispina in western Mexico.